PANDANGAN MASYARAKAT TENTANG PERNIKAHAN NGETAN-NGULON DI DESA WONOREJO KECAMATAN GUNTUR KABUPATEN DEMAK PERSPEKTIF ‘URF - FARIDATUN NISA; MASROKHIN (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The Ngetan-Ngulon wedding is a wedding tradition that is still preserved in Wonorejo Village, Guntur District, Demak Regency. This tradition prohibits Mbarep children from marrying someone whose home position is that the prospective groom is from the West and the bride is from the East, or vice versa. This research aims to determine the community's views on ngetan-ngulon marriages in Wonorejo Village. This research uses qualitative methods with an Empirical Sociology approach. Data was obtained through observation, interviews and documentation. The path taken in collecting data was field research. The informants for this research were community leaders, religious leaders, and married couples who married in the Ngetan-Ngulon tradition. The results of the research show that people's views about the Ngetan-Ngulon marriage are divided into two. First, people support this tradition because it is considered an ancestral tradition that brings blessings and harmony in the household. Second, people do not support this tradition because it is considered an outdated tradition and the good intentions of their children. Third, the perpetrator continued to carry out the Ngetan-Ngulon marriage, even though the community and even himself believed that the Ngetan-Ngulon marriage was prohibited. With the different views of one society from another, this has proven that the Value of 'Urf must be upheld at every level of society. Urf is not something final but rather a way to enforce inequality. The results achieved from this research are that the factors that cause the community to maintain the Ngetan-Ngulon marriage in Wonorejo Village are myth, economic, psychological, health, traditional and cultural factors and traditional figures are still used as role models for the habits inherited from their ancestors.